Standardization (translating and evaluating the validity and reliability) of the Speech, Spatial, and Qualities of Hearing Scale Questionnaire-12(SSQ12) to the Persian language - mahsa sepehrnejad; Farshid Rahimi; Nariman Rahbar; Mohammad Hossein Nilforoush; farnoosh Frajadi Rad (Shiraz University of Medical Sciences, 2022)
Background: This study aimed to prepare the Persian version of Speech, Spatial, and Qualities of Hearing Scale questionnaire-12 (SSQ-12-Persian version) and assess its validity and reliability to facilitate the effect of the usage of hearing aids on individuals using them.Methods: This study is considered an original research type of article. The questionnaire was translated to Persian according to WHO method. Firstly, two fluent Persian-speaking translators translated the questionnaire from Persian to English, and then three audiologists examined the questionnaire. The questionnaire was then translated from Persian to English and conceptually reviewed by two bilingual translators. Finally, 99 senior persons aged 22 to 52 years who used hearing aids and had their hearing thresholds assessed lately were given the Persian version of the Speech, Spatial, and Qualities of Hearing Scale 12 (SSQ-12) questionnaire. T-test examination and Cronbach Alpha were used to assess the reliability and validity and test-retest reliability.Results: Persian version of the SSQ-12 questionnaire showed high internal consistency (assessed by Cronbach Alpha = 0.924) and high test-retest (assessed by Cronbach Alpha = 0.868) reliability.Conclusion: SSQ-12 questionnaire is a comprehensive summary of the SSQ-49 questionnaire. It would be one of the valid questionnaires to evaluate hearing performance improvement in hearing aids users. The paired sample t-test revealed that the Persian version of the SSQ-12 questionnaire has good reliability and validity, and Cronbach's alpha revealed that the questionnaire has strong internal consistency (Cronbach's alpha =0.924).The reliability of the test-retest after a month was obtained, and the total scale result was 0.867. According to this study's results, SSQ-12 can be used as other Persian translated questionnaires like GHABP, SHQ, and IOI-HA for examining the effectiveness of hearing aids and their effects on limiting disabilities related to hearing loss.